Stunting pada Anak Bawah Tiga Tahun sebagai Tanda Bahaya (Red Flags) dalam Masa Pandemi COVID-19 - Gina Noor Djalilah (Universitas Muhammadiyah Surabaya, 2023)
Abstract Aware the COVID-19 pandemic period has made pre-young kids experience numerous impediments in addressing fundamental requirements because of multifactorial reasons for not exactly ideal development and advancement. The monetary emergency prior and then afterward the pandemic, the restrictions of assessment administrations when wiped out to the conclusion of routine essential wellbeing administrations. This happened practically 1 years 7 months until now and still ongoing. The effect felt by guardians straightforwardly and in a roundabout way about youngsters, particularly parts of not exactly ideal development require quick and concentrated treatment so the kid's development can be promptly sought after so it tends to be ideal. Stunting is Indonesia's challenge towards SDG'S 2020 which targets stunting rates to be smothered for brilliant ages to come. Red flags that lead to stunting should be recognized by parents so quick treatment can be completed on Indonesian kids.Keywords: Stunting, COVID-19, Toddler, Malnutrition, Children